Preventive Vaccinations of Respiratory Infections during Lung Transplantation - V. B. Polishchuk; K. V. Mashilov; A. A. Ryzhov (Эпидемиология и вакцинопрофилактика, 2020)
Relevance. Lung transplantation is recognized as a method of treating terminal stages of lung disease when the drug therapy resource has been exhausted. In addition to the lack of material for transplantation, a serious problem of lung transplantation is the low graft survival rate. The main reasons are infections and primary allograft failure. Aims. To consider the current state of the use of vaccine prophylaxis in the integrated management of patients before and after lung transplantation. Conclusions The prevention of respiratory infections in adult candidates for organ transplantation and recipients is recommended and included in many clinical protocols and recommendations, however, they are based mainly on studies performed on healthy individuals, and are poorly supported by the results obtained in the study of individuals who underwent complete internal organ transplantation. Also, the effectiveness of vaccination remains unexplored, taking into account the individual characteristics of the immune system and the state of population immunity in relation to vaccine-preventable infections.